Predictive Value of Alvarado Score and Ultrasound in the Diagnosis of Acute Appendicitis (A prospective study - Ahmed, Waleed Saadi; Tajer, Salah M.; Sayaly, Hend M. (Journal of the Faculty of Medicine Baghdad, 2021)
Background:  Acute appendicitis is the commonest non traumatic cause of acute abdominal pain that needs surgical management .Alvarado score and ultrasonographies are the most cost effective, easy and available aids for diagnosis. The aim of the study was determining   the reliability of Alvarado score and ultrasound in the diagnosis of acute appendicitis.Results: The study was applied with 100 cases with different types of abdominal pain at presentation with 51 males and 49 females .The sensitivity was97.3% ,specificity 90%, and accuracy  89 of combined usage of Alvarado score and U/S findings preoperatively.Patients and method:  A prospective non-interventional study including patients admitted with suggestive history with signs and symptoms of acute appendicitis to the surgical emergency ward of Baghdad teaching hospital from July 1st 2017 to Feb 10th 2018, Alvarado score calculated and ultrasonography done for each patient enrolled in this study, then to be followed for intraoperative findings.Conclusions: Combined application of Alvarado score and U/S has sensitivity 94.1% ,specificity 90% and accuracy 89% . In our medical facility and emergency ward, acute appendicitis remains as one of the top acute abdominal emergencies needing surgery in patients presenting with atypical clinical ﬁnding. So diagnosis becomes difﬁcult. So Alvarado score along with ultrasound findings are useful for increasing the reliability in emergency department for  accurate diagnosis of acute appendicitis therefore there should be training for the use of U/S by emergency physician and general surgeon in the diagnosis of acute appendicitis in order to decrease the rate of negative appendectomies .